2011
DOI: 10.5897/ajb11.501
|View full text |Cite
|
Sign up to set email alerts
|

Study on combining ability, heterosis and genetic parameters of yield traits in rice

Abstract: A study was conducted on heterosis, combining ability and genetic parameters of yield and yield components in rice. Five lines were crossed with two testers in line × tester manner to produce ten F 1 hybrids. Results show that general combining ability (GCA) effect was only significant for total number of kernels per panicle, number of filled kernels and grain yield per plant, and specific combining ability (SCA) effect was significant for yield and all of its studied components (except for 100-kernel weight).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…The hybrids K 2 -54 × Basmati 370, K 2 -9 × Komboka and K 2 -9 × PAN 84 had high parent heterosis for filled grains per panicle while K 2 -8 × Basmati 370 and K 2 -8 × 08FAN 10 had negative heterosis. These results are contrary to the findings of Mirarab et al (2011) who reported non-significant heterobeltiosis for filled grains per panicle. Positive heterobeltiosis in the hybrid IR58025A × IET18648 (49.73%) and standard heterosis of 141.1% over the check variety TTB404 for filled grains panicle -1 was reported (Tiwari et al, 2011;Borah et al, 2017).…”
Section: Filled Grains Per Paniclecontrasting
confidence: 99%
See 4 more Smart Citations
“…The hybrids K 2 -54 × Basmati 370, K 2 -9 × Komboka and K 2 -9 × PAN 84 had high parent heterosis for filled grains per panicle while K 2 -8 × Basmati 370 and K 2 -8 × 08FAN 10 had negative heterosis. These results are contrary to the findings of Mirarab et al (2011) who reported non-significant heterobeltiosis for filled grains per panicle. Positive heterobeltiosis in the hybrid IR58025A × IET18648 (49.73%) and standard heterosis of 141.1% over the check variety TTB404 for filled grains panicle -1 was reported (Tiwari et al, 2011;Borah et al, 2017).…”
Section: Filled Grains Per Paniclecontrasting
confidence: 99%
“…The parental lines such as Basmati 370, Basmati 217, PAN 84 and Komboka exhibited high and positive GCA effects for panicle length, flag leaf length, number of tillers plant -1 , number of spikelet's panicle -1 , number of panicles plant -1 and number of filled grains panicle -1 suggesting their desirability for improvement of positive agronomic and yield traits because they contributed to high grain yield, in contrast parents with low and negative GCA estimates (NERICA 1, PAN 84, K 2 -9, Dourado precoce and K 2 -54) are preferred for improvement of negative traits of grain yield such as plant height, 50% days to flowering and days to maturity. Previous studies reported the significance of using parents with high and positive GCA effects for the improvement of positive agronomic traits (Mirarab et al, 2011;Raju et al, 2014;Malemba et al, 2017). This study revealed high GCA variances for most of the yield traits studied.…”
Section: Evaluation Of Parents Based On Gca Effectssupporting
confidence: 48%
See 3 more Smart Citations